m | + | ( | m | − | 3 | ) | ÷ | 2 | = | 3 | − | ( | 2 | m | − | 1 | ) | ÷ | 3 |
方程左边 = | m | + | m | × | 1 2 | − | 3 | × | 1 2 |
= | m | + | m | × | 1 2 | − | 3 2 |
= | 3 2 | m | − | 3 2 |
3 2 | m | − | 3 2 | = | 3 | − | ( | 2 | m | − | 1 | ) | ÷ | 3 |
方程右边 = | 3 | − | 2 | m | × | 1 3 | + | 1 | × | 1 3 |
= | 3 | − | 2 3 | m | + | 1 3 |
= | 10 3 | − | 2 3 | m |
3 2 | m | − | 3 2 | = | 10 3 | − | 2 3 | m |
3 2 | m | + | 2 3 | m | = | 10 3 | + | 3 2 |
13 6 | m | = | 10 3 | + | 3 2 |
13 6 | m | = | 29 6 |
m | = | 29 6 | ÷ | 13 6 |
= | 29 6 | × | 6 13 |
= | 29 | × | 1 13 |
m | = | 29 13 |
m | = | 2.230769 |